ANALISIS VARIABILITAS CURAH HUJAN DI SUMATERA BARAT DAN SELATAN DIKAITKAN GENGAN KEJADIAN DIPOLE MODE - Eddy Hermawan; Sopia Lestari (Lembaga Penerbangan dan Antariksa Nasional, 2007)
The rainfall variability over the Western and Southern part of Sumatera Island related to te Dipole Mode (DM) event for period of twenty years (1980-1999) based on the monhly mean of rainfall, Dipole Mode Index (DMI), Sea Surface Temparature (SST), and Outgoing Longwave Radiation (OLR) data analysis have already investigated. By applying the spectral analysis technique Fast Fourier Transform (FFT), the most predominant peak ascillation of rainfall and DMI data has been identified. They are Semi Annual Oscillation (SAO) for Bukit Tinggi, Maninjau, and Sicincin sation, and Annual Oscillation (AO) for Padang-panjang, Padang, Batu Sangkar, Solok, Tabing, Bengkulu, Kotabumi, Jambi, and Palembang station, respectively. While the other predominant peak oscallation in period of 1.5 to 3 years are also found , especially on the DMI data analysis. It indicates that the rainfall variability over these areas could be related to the DM event, especially during DM (+) when the high pressure covers most of Indonesia region. When DM (+) occured, especially on JJA (June-July-August) and SON (September-October-November), the rainfall intensity over those area become less intil below normal condition. Conversely, when DM (-) occured, the amount of rainfall intensity is more than normal condition. Compared to DM (-), DM(+) looks more giving a significant influence to the rainfall in both areas.